Concrete Amnesia: Critical Regionalism as a Resistance Framework for Architectural Governance in the Kathmandu Valley - Maharjan, Sarita (NPRC Journal of Multidisciplinary Research, 2025)
Background: The Kathmandu Valley is witnessing a profound morphological crisis termed "Concrete Amnesia" the systemic erasure of indigenous Newari tectonic traditions in favor of a homogenized "Universal Civilization" of Reinforced Cement Concrete (RCC). This shift represents a rupture in cultural memory, replacing organic communal structures with rigid, profit-maximized forms.Objectives: This study aims to (1) analyze the "Policy Vacuum" regarding architectural character, (2) investigate the economic "Iron Triangle" (Speed, Cost, Labor) driving concrete adoption, and (3) propose a "Tectonic" governance framework that reconciles seismic safety with cultural identity.Methods: A qualitative multi-sited case study utilized legal-spatial analysis of building codes and a "Conflict Matrix" evaluation of three architectural typologies.Results: Governance prioritizes quantitative volume over qualitative character. Economic analysis indicates banking valuation models and labor migration render traditional craftsmanship unviable. Traditional courtyard models result in a 30% loss of rentable area compared to modern layouts.Conclusion: "Scenography" is a failed strategy. A "Tectonic" governance framework incentivizing the structural integration of the Chowk through specific FAR bonuses and market-creation for artisans is proposed to align economic profit with cultural preservation.Novelty: Unlike previous studies attributing heritage loss to cultural ignorance, this research identifies a structural causality: the correlation between the regulatory silence on aesthetics in national codes (NBC 105/206) and the economic penalties imposed by Floor Area Ratio (FAR) calculations. It integrates new theoretical lenses on "defamiliarization" to critique "Neo-Newari" kitsch and defines the traditional Chowk as a financial liability under current regimes. Crucially, it moves beyond the binary of "safe concrete vs. vulnerable tradition" to advocate for engineered vernacular resilience.